2017
DOI: 10.1177/0020764017737573
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial and detrimental effects of genetic explanations for addiction

Abstract: Background Addictions are highly stigmatized and increasingly construed as biomedical diseases caused by genes, partly to reduce stigma by deflecting blame. However, genetic explanations may have negative effects, which have been understudied in the context of addiction. How the effects of genetic explanations might differ for substance addiction versus behavioral addictions is also unknown. Aims This study examined the impact of genetic explanations for addiction on measures of treatment expectancies, blame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
37
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 43 publications
2
37
0
1
Order By: Relevance
“…After an extensive review of the literature, eight studies were identified that specifically assess the effects of receiving genotypic information for psychiatric conditions including depression, alcohol use disorder, and nicotine dependence (Dar-Nimrod, Zuckerman, & Duberstein, 2013;Gamm et al, 2004;Lebowitz & Ahn, 2017Lebowitz & Appelbaum, 2017;Lipkus, Schwartz-Bloom, Kelley, & Pan, 2015;Schiffman et al, 2016;Wilhelm et al, 2009). We excluded studies that provided genetic information for diseases related to nicotine use, such as lung cancer (Olfson et al, 2016;Smerecnik et al, 2012), or information related to alcohol metabolizing genes in the context of alcohol-related cancers (Johnson et al, 2016) in order to focus on the impact of genotypic information for psychiatric conditions.…”
Section: Impact Of Receiving Genotypic Informationmentioning
confidence: 99%
See 1 more Smart Citation
“…After an extensive review of the literature, eight studies were identified that specifically assess the effects of receiving genotypic information for psychiatric conditions including depression, alcohol use disorder, and nicotine dependence (Dar-Nimrod, Zuckerman, & Duberstein, 2013;Gamm et al, 2004;Lebowitz & Ahn, 2017Lebowitz & Appelbaum, 2017;Lipkus, Schwartz-Bloom, Kelley, & Pan, 2015;Schiffman et al, 2016;Wilhelm et al, 2009). We excluded studies that provided genetic information for diseases related to nicotine use, such as lung cancer (Olfson et al, 2016;Smerecnik et al, 2012), or information related to alcohol metabolizing genes in the context of alcohol-related cancers (Johnson et al, 2016) in order to focus on the impact of genotypic information for psychiatric conditions.…”
Section: Impact Of Receiving Genotypic Informationmentioning
confidence: 99%
“…However, a recent meta-analysis suggests the current literature provides little to no evidence that receiving genotypic information influences behavior (Hollands et al, 2016). There are also concerns that genotypic information may negatively impact individuals' behavior, self-efficacy, psychological state (Lawrence & Appelbaum, 2011;Lebowitz & Appelbaum, 2017), and physiology (Turnwald et al, 2019). These concerns are especially problematic since individuals seeking out personalized genotypic information may already be at high risk for psychiatric conditions (Kostick, Brannan, Pereira, & Lázaro-Muñoz,-2018).…”
Section: Introductionmentioning
confidence: 99%
“…This effect may even operate through the same psychological mechanism as the corresponding reductions in blame: if genetic and other biomedical explanations of mental disorders place patients’ psychiatric symptoms outside their control, it follows that the patients would be seen as less blameworthy but also as less empowered to overcome their psychopathology. Genetic and other biomedical explanations of mental disorders can also increase people’s confidence in the effectiveness of biomedical treatments (such as pharmacotherapy) but decrease their confidence in the effectiveness of “nonbiomedical” treatments (such as psychotherapy) …”
Section: Less Reassuring News About Psychosocial Impactsmentioning
confidence: 99%
“…Genetic and other biomedical explanations of mental disorders can also increase people's confidence in the effectiveness of biomedical treatments (such as pharmacotherapy) but decrease their confidence in the effectiveness of "nonbiomedical" treatments (such as psychotherapy). 9 Research among Symptomatic Individuals T he notion that biomedical explanations of mental disorders lead people to view others as unlikely to overcome their symptoms raises a parallel question with potentially significant implications: do such explanations also produce this kind of "prognostic pessimism" among people reflecting on the causes of their own psychiatric conditions? In recent years, a growing body of research has suggested an affirmative answer to this question.…”
mentioning
confidence: 99%
“…Una encuesta australiana sobre actitudes de la población general ha mostrado que conceptualizar la adicción como una enfermedad cerebral no está asociado a una menor estigmatización ni a un menor apoyo para el tratamiento involuntario u otros abordajes La adicción como enfermedad: ¿mitigando o alimentando el estigma? considerada (al alcohol o al juego) en el estudio (Lebowitz y Appelbaum, 2017).…”
unclassified